What Makes Health Care Special?: An Argument for Health Care Insurance - Horne, L. Chad (Kennedy Institute of Ethics journal, 2017)
, ABSTRACT:, While citizens in a liberal democracy are generally expected to see to their basic needs out of their own income shares, health care is treated differently. Most rich liberal democracies provide their citizens with health care or health care insurance in kind. Is this "special" treatment justified? The predominant liberal account of justice in health care holds that the moral importance of health justifies treating health care as special in this way. I reject this approach and offer an alternative account. Health needs are not more important than other basic needs, but they are more unpredictable. I argue that citizens are owed access to insurance against health risks to provide stability in their future expectations and thus to protect their capacities for self-determination.